As políticas de permanência na Unipampa: as especificidades das estudantes em período de maternidade - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This article addresses issues of gender inequality in the university environment, problematizing the social role of women who experience the condition of studentmother, pointing out the need for permanence policies in the lives of these students. In order to understand the challenges faced by student-mothers at the Universidade Federal do Pampa campus Itaqui, we analyze what kind of support they receive during their undergraduate studies, having to reconcile maternity and university life. It was sought to be anchored in the literature review and in autobiographical accounts, aiming to identify how the policies aimed at permanence in the university environment meet the specificities of student-mothers, highlighting the need for programs and aids that meet their demands. This is a qualitative approach, as it intends to explore the perception of those who experienced the investigated situation. Based on the results obtained, we conclude that despite the advances in the role of women in society, most of them face many difficulties, and that the students who become mothers during graduation are more likely to drop out of the course. It can be noticed that even with the aid made available by the institution, student-mothers still face difficulties in reconciling their academic life with motherhood, because some of this aid does not reach potential beneficiaries.
Keywords: Mulher; Estudantes mães; Políticas de permanência; Desigualdade de gênero; Women; Student mothers; Permanence policies; Gender inequality; CNPQ::CIENCIAS EXATAS E DA TERRA